PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS POWTOON BERBANTUAN MODELPROBLEM-BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Nita Khoirurohmah; Sri Wardani; Barokah Isdaryanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In 2020 the Ministry of Education, Culture, Research and Technology (Kemendikburistek) issued a policy regarding changes to the curriculum. Then in 2022-2023 the implementation of the new independent curriculum will be implemented in stages starting from class I and class IV. The implementation of the independent curriculum at SD Negeri Sampangan 01 Semarang City is carried out by the principal, teachers and students, as an initial program that follows recovery after the Covid-19 pandemic. The aim of this research is to develop, analyze the feasibility and test the effectiveness of learning videos based on the model-assisted PowerPoint model. problem based-learning in science and science subjects carried out in class IV of SDN Sampangan 01 Semarang. This research method uses research & development (R&D) developed by ADDIE. Data collection techniques use test, observation, interview and questionnaire techniques. The data that has been collected is then analyzed using several initial tests, namely the normality test and homogeneity test, while the final data analysis includes the t test and the N-gain test. The population in this study was 28 class IV students at SDN Sampangan 01 Semarang. The findings in this research show that product feasibility in every aspect is 80.43% media validation, 88.88% material validation, and 92.18% language validation. In the small group t-test, it was 16.473 > 2.570. Shows that there are differences in small group pretest and posttest learning outcomes. In the large group t-test, it was 48.752 > 2.079. Shows that there are differences in pretest and posttest learning outcomes for large groups. For the small group N-gain test it was 0.805 and the large group Ngain test was 0.780. These two values ​​show that there are pretest and posttest values ​​on learning outcomes using Powtoon-based learning videos assisted by the problem based-learning model. The conclusion is that Powtoon-based learning videos assisted by problem based learning models are feasible and effective for use in science and science learning.